Hydrated lime life-cycle assessment: Current and future scenarios in four EU countries. (1st October 2022) - Laveglia, Agustin; Sambataro, Luciano; Ukrainczyk, Neven; De Belie, Nele; Koenders, Eddie
Abstract: The environmental load associated to Hydrated Lime (HL) products is attributed to the limestone decomposition and the industrial production (combustion in the kiln, the electricity, the transports, etc.). Although the fuel and electricity mix used in the factory can be critical, no records of Life Cycle Assessment (LCA) have been found addressing this for HL. Considering the current environmental crisis, a shift to more sustainable sources of energy is expected. This paper studies, within the SUBLime EU network, the effect of the current fuel and electricity mix used in a HL plant, for Germany, Belgium, Portugal and Spain, as well as future scenarios. A theoretical Cradle-to-Gate Life Cycle Inventory for HL production was developed and used for scenario analysis, namely decarbonisation of the electricity matrix and replacement of hard coal by natural gas (NG) and biomass (B) in the fuel mix. The LCA for 2020 shows that, in 9 out of 15 indicators, the electricity consumption is significant. In terms of Global Warming Potential (GWP), 0.94 kg CO2 eq /kg HL are produced. Spain and Belgium have shown a better performance followed by Portugal and Germany. The results of future scenarios show that the shift to almost 100% renewable energies for electricity production reduce their sharing in almost all the indicators. As NG and B increase their proportion in the fuel mix, 9, 18 and 22% reductions in GWP in comparison to 2020 are achieved. However, 4 out of 15 indicators are higher than the reference due to the fuel mix. Highlights: IEA, 2020 in Europe an average of 0.94 kg CO2 eq /kg of Hydrated Lime are produced 9/15 indicators are sensitive to the electricity consumption in the plant In 2050, 4/15 indicators are higher than in 2020 due to the fuel mix The replacement of fossil solid fuel in the kiln allows up to 22% CO2 eq savings.